Embracing the heat: endovenous thermal ablation in chronic venous insufficiency - Kamran, Javeria; Imran, Maryum; Irfan, Rida; Noor Ul Huda; Akhtar, Ahmad (Journal of the Pakistan Medical Association, 2026)
Dear Fatema Jawad, Chronic Venous Insufficiency (CVI) is one of the most common diseases worldwide. It is classified using the CEAP classification system, the second component of which corresponds to varicose veins (VV).[1] It has a lower prevalence rate in developing countries compared to developed countries. However, in Pakistan, the reported prevalence rate is 16-20%, with a higher number of cases seen in older individuals and women, particularly pregnant women.[2] The pathophysiology results from weakened or damaged venous valves, specifically in the saphenous vein, leading to venous system malfunction and blood stasis, aggravated by standing or sitting for extended periods. It presents as painful swelling of the legs, VV, a needle-prick, a burning or tingling sensation, the feeling of heaviness or fatigue in the legs, spasms, and skin changes like hyperpigmentation and telangiectasia. Complications such as ulceration can arise if the condition is not managed promptly. Severe cases can lead to haemorrhagic shock, potentially resulting in death. [1,2] Mild CVI patients typically receive conservative management, including compression socks/ stockings and a healthier lifestyle recommendation, as well as pharmacological therapy, which can improve venous tone and capillary permeability.[3] Severe CVI, on the other hand, is treated through a well-established, highly effective, and minimally invasive surgical technique, i.e., Endo venous Thermal Ablation [ETA]. Its primary types currently in use are Endo Venous Laser Ablation (EVLA), Radiofrequency Ablation (RFA), and Steam Ablation. This procedure specifically targets the great and small saphenous veins, applying thermal energy that effectively seals and blocks the affected veins. In doing so, it redirects blood flow to healthier veins for improved venous return. As a result, the treated vein is gradually absorbed by the body over time. Other surgical options include open surgery for large dilated saphenous veins, aneurysmal enlargements, and removal of veins. In addition, ultrasound-guided foam sclerotherapy (UGFS) is another therapeutic intervention which is often used as it ensures patients experience lower levels of pain and fewer complications. The last resort for CVIs is catheter-based interventions. [3] Currently, RFA and sclerotherapy have shown promise in lower and middle-income countries. However, for patients in Pakistan, ETA will be more efficacious. This less-invasive technique has a reduced recovery time and is cost-effective. Moreover, it grants increased mobility and has fewer postoperative complications. The post-procedural pain can be controlled by analgesics. [4] Pulmonary embolism and venous thromboembolism are some of the severe postoperative outcomes of these therapeutic advances —Continue